Application of Accounting Information System and Income Accountability for Replacement of Damaged Passports at the Regional Office of the Ministry of Law and Human Rights, South Sumatra - resky nurhidayah; Leriza Destima Anggraini; Vhiika Meiriasari (International Journal of Community Service & Engagement, 2022)
This study aims to investigate the effects of the accounting information system and accountability on passport replacement incomeat the Ministry of Law and Human Rights of South Sumatra. The population was all 152 employees at the Ministry of Law and Human Rights. This study collected data by distributing questionnaires to 48 respondents. Data were analyzed using multiple linear regression with SPSS software version 23.The results revealed that the partial test using the t-test, the accounting information system variable has a t count of 2.625 with a significance of 0.000 below the 0.05 significance. Thus, t count > t table or 2,625 > 1,677. Thus, it can be concluded that the accounting information system affects the passport replacement income. These results prove that the hypothesis is accepted, the accounting information system has a significant effect on replacement of damaged passports, and the effect of damaged passport income accountability shows that the accountability variable has a t count of 2.827 with a significance of 0.003 below the significance of 0.05. Thus, t count > t table or 2.827 > 1.677. Therefore, it can be concluded that accountability affects the passport replacement income. These results prove that the hypothesis is accepted, accountability has an effect on replacing damaged passports.